2021
DOI: 10.24275/rmiq/ia2063
|View full text |Cite
|
Sign up to set email alerts
|

Native fungal strains from Yucatan, an option for treatment of biomethanated vinasse

Abstract: Modelado de la biodegradación en biorreactores de lodos de hidrocarburos totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In this regard, Montoya et al [2] reported color removal when treating TVs in two types of constructed wetlands (horizontal subsurface flow wetlands and vertical upflow wetlands) of approximately 86%, which they attributed to a probable biodegration by the bacterial population that grows mainly near the rhizomes of CW plants [36]. With respect to the VDFW-LF, a higher removal was expected, since there are investigations where a reduction in the color of distillery residues has been reported [37,38]. These color reductions have been attributable to processes such as absorption on the mycelium or due to the enzymatic and extracellular activity (of laccase, manganese peroxidase and lipase) that characterizes fungi.…”
Section: Apparent Color Turbidity and True Colormentioning
confidence: 99%
“…In this regard, Montoya et al [2] reported color removal when treating TVs in two types of constructed wetlands (horizontal subsurface flow wetlands and vertical upflow wetlands) of approximately 86%, which they attributed to a probable biodegration by the bacterial population that grows mainly near the rhizomes of CW plants [36]. With respect to the VDFW-LF, a higher removal was expected, since there are investigations where a reduction in the color of distillery residues has been reported [37,38]. These color reductions have been attributable to processes such as absorption on the mycelium or due to the enzymatic and extracellular activity (of laccase, manganese peroxidase and lipase) that characterizes fungi.…”
Section: Apparent Color Turbidity and True Colormentioning
confidence: 99%
“…Laccase (EC 1.10.3.2) is a blue multi-copper oxidase that catalyze the oxidation of phenolic and nonphenolic substrates with the reduction of one molecule of oxygen to two molecules of water (Liu et al, 2020;Mayolo-Deloisa et al, 2020). Laccases have potential application in food and pharmaceutical industry processes, in water and soil bioremediation, bleaching of paper pulp, decolorization of dyes in textile industry and in lignin degradation for production of biofuels (Arregui et al, 2019;Bertrand et al, 2013;España-Gamboa et al, 2021;Liu et al, 2020;Mayolo-Deloisa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%